2) To solve the given equation, fill the boxes
2
x-1
y -
Let
= m
letan
New equation
6m - 3n = 1
On solving
m=
n =
replacing m, n their original value
On solving
X-3
3
x=
y=
0
Answers
Answered by
1
Answer:
In △ABC AB=AC
⇒∠B=∠C (Angles opposite to equal sides are equal)
Now using angle sum property
∠A+∠B+∠C=180
∘
⇒80
∘
+∠C+∠C=180
∘
⇒2∠C=180
∘
−80
∘
⇒∠C=
2
100
∘
=50
∘
now ∠C+∠x=180
∘
(Angles made on straight line (AC) are supplementary)
⇒50
∘
+∠x=180
∘
⇒∠x=180
∘
−50
∘
=130
∘
@ARSH(◕ᴥ◕)
insta@_arsh_deep_29
(✪㉨✪)
Similar questions